Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1155/2017/3057495
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in Cancer Patients during18F-FDG PET/CT Low Dose: A Comparison of Anxiety Levels before and after Imaging Studies

Abstract: Objective. Assessing the level of anxiety in oncology patients who underwent 18F-FDG PET/CT low dose scan and identifying the main reasons that generate anxiety. Material and Method. The study included 81 cancer patients submitted to the 18F-FDG PET/CT low dose scan. Patients filled in the Scan Experience Questionnaire and the State-Trait Anxiety Inventory (STAI) before and after 18F-FDG PET/CT low dose scan. Results. Substantial levels of anxiety were detected both before and after 18F-FDG PET/CT low dose sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…The lowest satisfaction concerned how the patients would receive the results of the examination. This finding is similar to another study revealing that patients may experience anxiety during 18 F-FDG PET/CT, mainly because of fear of the results (6), and indicates the importance of having the nurses who execute the examination make sure patients understand how they will receive the results. Some patients experienced discomfort during the 18 F-FDG PET/CT examination, especially regarding the time spent in the scanner and the need to maintain a fixed body position, as is consistent with our previous findings (4,10).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The lowest satisfaction concerned how the patients would receive the results of the examination. This finding is similar to another study revealing that patients may experience anxiety during 18 F-FDG PET/CT, mainly because of fear of the results (6), and indicates the importance of having the nurses who execute the examination make sure patients understand how they will receive the results. Some patients experienced discomfort during the 18 F-FDG PET/CT examination, especially regarding the time spent in the scanner and the need to maintain a fixed body position, as is consistent with our previous findings (4,10).…”
Section: Discussionsupporting
confidence: 87%
“…PET/ CT with the radioactively labeled glucose analog 18 F-FDG is used in oncology imaging and has proven valuable for diagnosis, staging, and evaluation of therapy response (1)(2)(3). Oncologic patients who undergo 18 F-FDG PET/CT may experience discomfort during time spent in the PET/ CT scanner (4), anxiety before the procedure (5), or anxiety after the procedure because of fears concerning the results (6).…”
mentioning
confidence: 99%
“…Each scale has 20 affirmations for which the volunteers indicate the intensity at that time (STAI—E) and the frequency with which they occur (STAI—T) through a scale of 1 to 4 points. The result is a numerical value and the total score of each scale ranges from 20 to 80 points [ 43 ]. The results of the scores were classified according to Mayer et al (2016) [ 44 ] in three types of anxiety levels: low anxiety (< 33 points), moderate anxiety (33 to 49 points), and high anxiety (> 49 points).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] An increasing number of cancer patients are required to undergo PET/CT examination. However, many studies have demonstrated that patients experienced a high level of anxiety during PET/CT examination because of a variety of reasons, 5,6 such as the use of radiopharmaceuticals and uncertain of the scan results. A study reported that patients were more anxious when undergoing the PET/CT scan than risky treatments.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] However, another study reported that more information provided by technologist only made people feel satisfied but did not reduce their anxiety levels. 5 One study indicated that patients who were given more detailed information about the adverse effects of radiation exposure generated higher anxiety levels. 6 According to these inconsistent results, exploring other methods to reduce patient anxiety levels is urgently needed.…”
Section: Introductionmentioning
confidence: 99%